Research Progress of Halide Perovskite Nanocrystals in Biomedical Applications: A Review - Guiyun Wang; Yanxia Qi; Zhiyan Zhou; Zhuang Liu; Ruowei Wang (Inorganics)
Halide perovskite nanocrystals have rapidly emerged as a prominent research topic in materials science over the past decade owing to their exceptional optoelectronic properties and tunability. Their distinctive characteristics, including high light absorption coefficients, high quantum yields, narrow-band emissions, low defect densities, and adjustable chemical compositions and sizes, position them as highly promising candidates for applications in optoelectronic devices, energy conversion units, and other related systems. However, due to the toxicity and instability of halide perovskite nanocrystals, their widespread application in the biomedical field has been limited in the past. In recent years, numerous innovative coating strategies have been reported to effectively enhance the stability of halide perovskite nanocrystals while confining their toxic metal ions within the coating layers, thereby significantly improving their biocompatibility. This review provides a comprehensive summary of the recent progress of halide perovskite nanocrystals in the field of biomedicine. It covers coating strategies to enhance stability and biocompatibility, as well as the applications of coated halide perovskite nanocrystals in biomedicine, with a particular focus on their unique advantages in bioimaging and chemical sensing. Finally, we address unresolved issues and challenges, such as the metabolic pathways and final products of halide perovskite nanocrystals in vivo. We hope to inspire researchers in the field and provide direction for future studies.